Nerve Entrapment in Ankle and Foot: Ultrasound Imaging - Chari, Basavaraj; McNally, Eugene (Seminars in Musculoskeletal Radiology, 2018)
Peripheral nerve entrapment of the ankle and foot is relatively uncommon and often underdiagnosed because electrophysiologic studies may not contribute to the diagnosis. Anatomy of the peripheral nerves is variable and complex, and along with a comprehensive physical examination, a thorough understanding of the applied anatomy is essential. Several studies have helped identify specific areas in which nerves are commonly compressed. Identified secondary causes of nerve compression include previous trauma, osteophytes, ganglion cysts, edema, accessory muscles, tenosynovitis, vascular lesions, and a primary nerve tumor. Imaging plays a key role in identifying primary and secondary causes of nerve entrapment, specifically ultrasound (US) and magnetic resonance imaging. US is a dynamic imaging modality that is cost effective and offers excellent resolution. Symptoms of nerve entrapment may mimic other common foot and ankle conditions such as plantar fasciitis.
Keywords: peripheral nerve entrapment; ultrasound of foot and ankle nerve entrapment; ultrasound of peripheral nerve impingement; Baxter's neuropathy; tarsal tunnel syndrome